Produksi Biodiesel Dari Minyak Nyamplung Menggunakan Katalis Lempung; Pengaruh Rasio Mol Minyak : Metanol Dan Konsentrasi Aktivasi Katalis - Husna, Zakiyatul; Bahri, Syaiful; Khairat, Khairat (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Biodiesel is one of alternative energy to replace fossil fuels from vegetable oil. The aims of this research were to produce biodiesel from callophylum oil using heterogen catalyst clay, determine the characteristics of the activated clay catalyst, determine the optimal conditions of making biodiesel from callophylum oil, determine the physical and chemical properties of biodiesel produced,comparing the characteristics of physics biodiesel synthesized by standards SNI 1782-2015.Catalyst is made by grinding the clay palas to a size of -100 + 200 mesh. Clay was activated using H2SO4 solution with variation of concentrations 0,5 N, 1 N and 2 N. The mixture is filtered using a vacuum pump and calcined at 300ÂºC for 3 hours. Production of biodiesel is carried out through two stages: esterification and trans-esterification. Before esterification, degumming process was done to remove impurities and gum contained in the oil. While in the trans-esterification process, variation in the mole ratio of oil : methanol is 1:6, 1:9 and 1:12, callophylum oil sample weight 50 gram and 1% by weight of clay catalyst added to the to trans-esterification reactor, reaction lasted for 120 minutes at 60ÂºC with agitation speed 400 rpm. This research resulted in the largest biodiesel yield on the use of the activation of the acid concentration 2N variation mole ratio of oil : methanol 1:9 is 86.2 %. The Characteristics of the catalyst that has a surface area and ratio of Si/Al large enough that 25,74 and 37,64 (m2/g) with biodiesel produced almost in accordance with established standards (SNI 04-1782-2015). Keywords: biodiesel, callophylum oil, palas clay, transesterification